Relaxor-like behavior and ferroelectric evolution in (1-x)[0.5BZT−0.5PT]−(x)BKT ternary system - Prasatkhetragarn A. (2017)
© 2016 Taylor & Francis Group, LLC. The ferroelectric materials with high Curie temperature in (1-x)[0.5Bi(Zn 0.5 Ti 0.5 )O 3 − 0.5PbTiO 3 ]−(x)[(Bi 0.5 K 0.5 )TiO 3 ] or (1-x)[0.5BZT−0.5PT] −(x)BKT ternary system were synthesized by solid state reaction technique. The single phase perovskite was formed at 950°C in compositions with x ≥ 0.50. The dielectric properties (ϵ r and tan δ) were observed to exhibit the relaxor-like behavior. From room temperature P–E measurement, both P r and E c were found to increase with increasing BKT content.